Evaluation of the Impact of the Community Water Supply and Sanitation Program (PAMSIMAS) in Stabat Lama Village, Kec. Wampu, Kab. Langkat - Mubarok, Ibnu Rizal; Yafiz, Muhammad (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The problem of clean water is one of the problems that often occurs in various regions in Indonesia. The problem of clean water that occurs is followed by a poor water sanitation system. One of the areas experiencing clean water problems is Stabat Lama Village, Kab. Langkat. To overcome these problems, the government has implemented the Community Water Supply and Sanitation Program (PAMSIMAS). The existence of the PAMSIMAS program is expected to help residents access clean water. The purpose of this study was to determine the impact that PAMSIMAS had on the village community of Stabat Lama and also what factors supported and hindered community participation in the PAMSIMAS Program. The method used in this research is descriptive qualitative. The findings of this study indicate that the existence of PAMSIMAS has had an impact on lifestyle and social interaction in the community. In addition, there are several supporting factors in community participation including the establishment of cooperation between the community and local officials and the availability and ease of information to the community regarding the management of PAMSIMAS. The inhibiting factors for community participation are the limited information on the program that was launched due to the tight regulation of program arrangements, the lack of understanding between the community and the government in managing PAMSIMAS, and the PAMSIMAS program administration system which tends to be less involved with the community in program implementation